Establishing a successful rat model of duodenal- jejunal bypass: A detailed guide. (August 2019) - Akalestou, Elina; Genser, Laurent; Villa, Francesco; Christakis, Ioannis; Chokshi, Shilpa; Williams, Roger; Rubino, Francesco
Gastric bypass surgery, an operation that restricts the stomach and bypasses the duodenum and part of the jejunum, results in major improvement or remission of type 2 diabetes. Duodenual-jejunal bypass was developed by one of the authors (FR) as an experimental, stomach-sparing variant of gastric bypass surgery to investigate weight-independent mechanisms of surgical control of diabetes. Duodenual-jejunal bypass has been shown to improve various aspects of glucose homeostasis in rodents and in humans, thus providing an experimental model for investigating mechanisms of action of surgery and elusive aspects of gastrointestinal physiology. Performing duodenual-jejunal bypass in rodents, however, is associated with a steep learning curve. Here we report our experience with duodenual-jejunal bypass and provide practical tips for successful surgery in rats. Duodenual-jejunal bypass was performed on 50 lean rats as part of a study aimed at investigating the effect of the procedure on the physiologic mechanisms of glucose homeostasis. During the study, we have progressively refined details of anatomic exposure, technical aspects of duodeno-jejunostomy and peri-operative care. We analysed the role of such refinements in improving operative time and post-operative mortality. We found that refinement of exposure methods of the gastro-duodenal junction aimed at minimizing tension on small visceral vasculature, technical aspects of duodeno-jejunal anastomosis and peri-operative management played a major role in improving the survival rate and operative time. Overall, an experimental model of duodenual-jejunal bypass was successfully reproduced. Based on this experience, we describe here what we believe are the most important technical tips to reduce the learning curve for the procedure.